Breathless - McCulloch, Amy, 1986- (Anchor Books, a Division of Penguin Random House, LLC, 2022)
"Journalist Cecily Wong is in over her head. She's come to Mount Manaslu, the eighth highest peak in the world, to interview internationally famous mountaineer Charles McVeigh on the last leg of a record-breaking series of summits. She's given up everything for this story--her boyfriend, her life savings, the peace she's made with her climbing failures in the past--but it's a career-making opportunity. It could finally put her life back on track. But when one climber dies in what everyone else assumes is a freak accident, she fears their expedition is in danger. And by the time a second climber dies, it's too late to turn back. Stranded on a mountain in one of the most remote regions of the world, she'll have to battle more than the elements in a harrowing fight for survival against a killer who is picking them off, one by one"--